2005
DOI: 10.5713/ajas.2005.1440
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation with Branched-chain Amino Acids (BCAAs) during Nursing on Plasma BCAA Levels and Subsequent Growth in Cattle

Abstract: To determine the effects of short-term dietary supplementation of branched-chain amino acids (BCAAs) during nursing (from 3 to 28 days of age) on plasma BCAA levels and subsequent growths in cattle, 12 nursing male Holstein calves, randomly assigned to control and treatment groups (n = 6 in each group), orally received a daily supplement of essential BCAAs (2 g/kg body weight/day; 1:1:1 of valine, leucine and isoleucine) or not. The plasma BCAA levels increased linearly after the administration. During the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Branched-chain amino acids are important for muscle growth, particularly in growing cattle. A study conducted by Li and others examined the effects of BCAA supplementation during nursing on the ADG of growing dairy cattle from three to twenty-eight days after birth [46]. The authors observed that the steers that received the treatment during the first four weeks of life had sustained greater ADG than the control group starting at two months of age through slaughter at eighteen months of age [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Branched-chain amino acids are important for muscle growth, particularly in growing cattle. A study conducted by Li and others examined the effects of BCAA supplementation during nursing on the ADG of growing dairy cattle from three to twenty-eight days after birth [46]. The authors observed that the steers that received the treatment during the first four weeks of life had sustained greater ADG than the control group starting at two months of age through slaughter at eighteen months of age [46].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Li and others examined the effects of BCAA supplementation during nursing on the ADG of growing dairy cattle from three to twenty-eight days after birth [46]. The authors observed that the steers that received the treatment during the first four weeks of life had sustained greater ADG than the control group starting at two months of age through slaughter at eighteen months of age [46]. The treatment group had, on average, a 14.8% greater final body weight at slaughter than the control group [46].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the present study, Wang et al [ 27 ] measured the concentrations about 24 h after feeding AA. Li et al [ 32 ] demonstrated that serum BCAA of Holstein calves (28 d of age) exhibited the postprandial peak 6 h after feeding BCAA, and those concentrations returned to baseline concentrations that were similar to the concentration in control calves 18 h after feeding. The decreased serum BHB of GLN vs. CTL could be more of a result of a decline in fatty acid mobilization from adipose tissues [ 33 , 34 ] than a volatile fatty acid production decline in the rumen because the SFI of GLN and CTL were similar in the first week during weaning.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in rumen fermentation products (ammonia, total volatile fatty acid, acetate, and propionate) in OPF supplemented with sakura block plus was due to the high content of branched amino acids (valine, leucine, and isoleucine) in earthworms (Hayati et al, 2011) and it has a role in increasing the synthesis and growth of rumen microbes (Li et al, 2005;Zain et al, 2008;Zhang et al, 2013). Valine, leucine, and isoleucine undergo decarboxylation and deamination to produce Branched Chain Volatile Fatty Acid (BCVFA) (Andries et al, 1987).…”
Section: Advances Inmentioning
confidence: 99%
“…The results of this study showed that sakura block plus as supplement feed enriched with earthworm flour has a positive impact on increasing the degradation and digestibility value of high-fiber palm oil feed. Earthworms as a source of protein and sources of branched amino acids are excellent for increasing the growth of rumen microbes which have a major role in degrading fibrous feed to produce volatile fatty acids, biomass, and gases (Li et al, 2005;Zain et al, 2008;Zhang et al, 2013). Wang et al (2008) stated that feed derived from agricultural and plantation waste such as palm oil palms generally contains very low-branched amino acids so that it can reduce the growth rate of rumen microbes.…”
Section: The Effect Of Sakura Block Plus On Nutrient Digestibilitymentioning
confidence: 99%